2009
DOI: 10.1016/j.taap.2008.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial respiration and protein nitration in the rat hippocampus after acute inhalation of combustion smoke

Abstract: Survivors of massive inhalation of combustion smoke endure critical injuries, including lasting neurological complications. We have previously reported that acute inhalation of combustion smoke disrupts the nitric oxide homeostasis in the rat brain. In this study, we extend our findings and report that exposure to smoke induces protein nitration in the rat hippocampus and that mitochondrial proteins are a sensitive nitration target in this setting. Mitochondria have central roles in energy metabolism and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 56 publications
(64 reference statements)
1
31
0
Order By: Relevance
“…Accordingly, brain manifestations of acute exposure to combustion smoke span a broad range of adversely affected targets (Lee et al, 2005; Lee et al, 2009; Zou et al, 2009; Lee et al, 2010; Lee et al, 2011; Zou et al, 2013) and we sought to identify those targets, which are protected by neuroglobin in this setting. To this end, we first produced a transgenic mouse with neuron-specific overexpression of Ngb and demonstrated that Ngb protects primary neurons by raising the threshold of nitric oxide mediated neuronal injury (Singh et al, 2013) and that in vivo, elevated Ngb attenuates the formation of smoke-induced oxidative DNA damage in the mouse brain (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, brain manifestations of acute exposure to combustion smoke span a broad range of adversely affected targets (Lee et al, 2005; Lee et al, 2009; Zou et al, 2009; Lee et al, 2010; Lee et al, 2011; Zou et al, 2013) and we sought to identify those targets, which are protected by neuroglobin in this setting. To this end, we first produced a transgenic mouse with neuron-specific overexpression of Ngb and demonstrated that Ngb protects primary neurons by raising the threshold of nitric oxide mediated neuronal injury (Singh et al, 2013) and that in vivo, elevated Ngb attenuates the formation of smoke-induced oxidative DNA damage in the mouse brain (Lee et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously developed combustion smoke-inhalation model for the awake rodent (Lee et al, 2005; Chen et al, 2007; Lee et al, 2009; Lee et al, 2010; Lee et al, 2011). Male CB57BL/6 mice (25–30 gram) wild type and transgenic (Ngb-tg), with neuron specific overexpression of neuroglobin under the control of rat synapsin 1 promoter were used (Lee et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal studies have shown that oxidative DNA damage caused by inhibition of mitochondrial respiratory complexes may contribute to neuronal dysfunction and progressive brain injury 1 3. The patient's course of illness between 3 and 14 years after inhalation injury may have resulted, in part, from impaired mitochondrial respiration and oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…There was no scientific or mechanistic explanation that confirmed this suggestion nor was it associated with a systemic overproduction of free radicals. The basis of the discussion was reverted to animal studies, which had established a nonphysiological environment that was causal for increased ROS production, inhibition of mitochondrial respiration and oxidative DNA damage (12)(13)(14). Such investigations reinforce and reiterate that oxidative damage does not occur under normal physiological conditions.…”
Section: Is Oxidative Damage Involved In Depressive Disorder?mentioning
confidence: 99%